Hypertension Awareness Reciprocal Assistance Through SENSI (Senam Lansia) In Elderly With Healthy Lifestyle - Puspodari; Nur Ahmad Muharram; Dhedhy Yuliawan; Septyaning Lusianti; Reo Prasetiyo Herpandika; Rendhitya Prima Putra; Weda; Slamet Junaidi; Adinda Aprilia Agasa (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Hypertension is the number one cause of death in the world every year. Hypertension is one of the common cardiovasycular diseases and the most common in the community. Hypertension is called the “silent killer” because it often comes without symptoms. Elderly people are at risk of developing hypertension because as they get older, blood pressure tend to increase. Therefore, there is a need for knowlwdge for the elderly to maintain a healthy lifestyle and do elderly exercise to prevent hypertension. This reciprocal assistance on hypertension awareness throught SENSI (Senam Lansia) is expected to improve health and maintain the health of the elderly in the Bangsongan Health Center. The achievement target in this activity is to increase the knowlwdge of the elderly about how to prevent hypertension and to do elderly exercise regulary either independently or together. After mentoring, the elderly know how to prevent hypertension and are enthusiastic about participating in the elderly gymnastics program as aroutine activity. The elderly who participated in the mentoring felt enthusiastic about participating in gymnastics and would do gymnastics as a routine physical activity at home.